2011
DOI: 10.2478/v10195-011-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Drivers’ Age, Gender, Driving Experience, and Aggressiveness as Predictors of Aggressive Driving Behaviour

Abstract: Recent years have seen a growing interest in the problem of aggressive driving. In the present study two demographic variables (gender and age), two non-psychological driving-experience related variables (annual mileage and legal driving experience in years) and aggressiveness as a personality trait (including behavioural and affective components) as psychological variable of individual differences were examined as potential predictors of aggressive driving. The aim of the study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Considering the fact that the higher the SRT, the smoother the driver's braking behavior to yield to the cyclist, this result highlights that older drivers are expected to adopt less abrupt yielding maneuver compared to younger drivers. This finding was consistent with previous studies [47][48][49], in which the correlation analysis proved that the driver's age has a statistically significant negative correlation with the aggressive driving behavior.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the fact that the higher the SRT, the smoother the driver's braking behavior to yield to the cyclist, this result highlights that older drivers are expected to adopt less abrupt yielding maneuver compared to younger drivers. This finding was consistent with previous studies [47][48][49], in which the correlation analysis proved that the driver's age has a statistically significant negative correlation with the aggressive driving behavior.…”
Section: Discussionsupporting
confidence: 93%
“…It has been previously reported that driver factors are directly or indirectly responsible for approximately 90% of traffic accidents. 25 , 26 , 83 , 84 The recognition of risky drivers prone to aggressive driving behaviors and accident involvement is essential for ensuring traffic and public safety. It has previously been asserted that drivers’ self-reporting accurately represents their actual behavior, 85 especially when surveys were conducted anonymously, 86 inferring that findings from this anonymous survey would be reliable.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the current study elucidated that age and aggressive driving behavior was negatively correlated, consistent with previous studies that elderly drivers were safer drivers and in comparison, younger drivers were prone to commit increasingly risk-taking driving. 26 , 27 , 87 However, the above studies ignored that other variables interacted with age during global traffic environment. Zhang analyzed the interaction of age and sex on aggression, and found the converse trend that aggressive driving increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the differences in driver aggression, aberrant, and positive driver behaviors between the five countries, ANCOVA was used after controlling for age, gender, and frequency of traveling as a driver in a passenger car. Zhang, Qu, Ge, Sun, and Zhang (2017) report that age influences driving behaviors while many studies have found a negative correlation between age and aggressive driving (Dahlen & White, 2006;Krahé, 2005;Krahé and Fenske, 2002;Perepjolkina and Ren ßģe, 2011;Wickens, Mann, Stoduto, Ialomiteanu, & Smart, 2011). Similarly, Wickens et al (2012) argue that gender is an impor- tant factor to understand driver anger and aggression.…”
Section: Discussionmentioning
confidence: 99%